An investigation of the effect of operational conditions on a sequential extraction procedure for arsenic in soil in Thailand - Chatchai Srithongkul (2020)
© 2019 Elsevier Ltd Sequential Extraction Procedure (SEP) can be used to evaluate the toxicity characteristics of heavy metals in soil, including arsenic (As), by separating the metals into several different fractions using selective extraction solvents in sequence. To accomplish this separation task, various factors that are known to affect the extraction process should be carefully considered. This research aimed to investigate the effect of the operational conditions on the SEP for As in soil using experimental designs. In the first step, a Plackett-Burman design was used twice to screen the important extraction variables from a total of 19 studied variables. As a result, SSR, extraction time of the first fraction (F1), and concentrations of sodium acetate (NaOAc) in F2 and ammonium oxalate (NH4Ox) in F6 were identified as significant to the amount of the extracted As. The selected variables were further investigated using a central composite design with response surface methodology. The optimized SEP characterized by 1:75 g:mL of SSR, an extraction time of 7 h 20 min of F1, 0.16 M of NaOAc and 0.11 M of NH4OAc were applied to extract a sample from contaminated agricultural soil obtained from the north of Thailand. The fractionation result was compared with the result obtained from a previously reported SEP method. It was found that similar extraction results could be achieved (91–97% As recovery). However, the optimized method revealed certain advantages in that it required dramatically less operation time (from 68 h to 32 h) and lower concentrations of the extraction solvents.